Urban Disposal from Civil Construction and its Relation With Public Health - Bueno, Laura Machado de Mello; Vaz, Mariana Alves; Vaz, Mariana Alves; Cerejo, Lucas Nakamura (National Journal of City Management, 2024)
This study explores the link between the management of construction waste and the incidence of dengue in Campinas, highlighting the importance of sustainable practices and the role of public authorities. Between 2018 and 2021, the exemption from the onerous grant of the right to build indicated a possible increase in construction activity, coinciding with the growth of dengue cases, exacerbated by atypical climatic events and floods that created areas conducive to the proliferation of the Aedes aegypti mosquito. By analyzing data on issued permits, dengue case records, and rainfall, the study seeks to understand how urban and environmental dynamics affect public health. It emphasizes the need for an integrated approach that involves public policies, solid waste management techniques, and community awareness to discuss the risks of dengue proliferation in urban areas.
Keywords: Solid Waste; Water in the Urban Environment; Aedes aegypti